CREBBP cooperates with the cell cycle machinery to attenuate chidamide sensitivity in relapsed/refractory diffuse large B-cell lymphoma. (28th November 2021) - Sun, Yichen; Gao, Yan; Chen, Jianfeng; Huang, Ling; Deng, Peng; Chen, Jinghong; Chai, Kelila Xin Ye; Hong, Jing Han; Chan, Jason Yongsheng; He, Haixia; Wang, Yali; Cheah, Daryl; et al.
Abstract: Diffuse large B-cell lymphoma (DLBCL) exhibits frequent inactivating mutations of the histone acetyltransferase CREBBP, highlighting the attractiveness of targeting CREBBP deficiency as a therapeutic strategy. In this study, we demonstrate that chidamide, a novel histone deacetylase (HDAC) inhibitor, is effective in treating a subgroup of relapsed/refractory DLBCL patients, achieving an overall response rate (ORR) of 25.0% and a complete response (CR) rate of 15.0%. However, the clinical response to chidamide remains poor, as most patients exhibit resistance, hampering the clinical utility of the drug. Functional in vitro and in vivo studies have shown that CREBBP loss of function is correlated with chidamide sensitivity, which is associated with modulation of the cell cycle machinery. A combinatorial drug screening of 130 kinase inhibitors targeting cell cycle regulators identified AURKA inhibitors, which inhibit the G2/M transition during the cell cycle, as top candidates that synergistically enhanced the antitumor effects of chidamide in CREBBP -proficient DLBCL cells. Our study demonstrates that CREBBP inactivation can serve as a potential biomarker to predict chidamide sensitivity, while combination of an AURKA inhibitor and chidamide is a novel therapeutic strategy for the treatment of relapsed/refractory DLBCL. Highlights: The ORR of relapsed/refractory DLBCL patients to chidamide treatment reaches 25.0%. CREBBP is a potential predictive biomarker for chidamide in DLBCL. Chidamide resistance is dependent on the cell cycle machinery. AURKA inhibitor overcome chidamide resistance in CREBBP proficient DLBCL.